Thiourea-Catalyzed Domino Michael–Mannich [3+2] Cycloadditions: A Strategy for the Asymmetric Synthesis of 3,3′-Pyrrolidinyl-dispirooxindoles - Zhi, Ying; Zhao, Kun; von Essen, Carolina; Rissanen, Kari; Enders, Dieter (Synlett, 2017)
The asymmetric synthesis of trifluoromethylated 3,3′-pyrrolidinyl-dispirooxindole derivatives with four contiguous stereogenic centers, including two vicinal spiro-stereocenters, is described. Employing a bifunctional thiourea catalyst, a domino Michael–Mannich [3+2] cycloaddition occurs readily between isatin ketimines and isatin-derived enoates with good yields and very high stereoselectivities, providing a direct entry to the title compounds of potential medical value.
Keywords: asymmetric synthesis; dispirooxindole; organocatalysis; domino reaction; Michael–Mannich [3+2] cycloaddition